THE SEMANTIC ANALYSIS OF PHRASEOLOGICAL UNITS EXPRESSING POSITIVE AND NEGATIVE CHARACTER TRAITS IN THE UZBEK LANGUAGE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the semantic features of Uzbek phraseological units used to express positive and negative character traits. Through the analysis of structural forms, metaphorical components, and cultural meanings, the study demonstrates how these expressions embody the moral and psychological worldview of Uzbek speakers.